A P3A-Type ATPase and an R2R3-MYB Transcription Factor Are Involved in Vacuolar Acidification and Flower Coloration in Soybean - Sundaramoorthy, Jagadeesh; Park, Gyu Tae; Lee, Jeong-Dong; Kim, Jeong Hoe; Seo, Hak Soo; Song, Jong Tae (Frontiers in Plant Science, 2020)
The determination of flower color mainly depends on the anthocyanin biosynthesis pathway and vacuolar pH; however, unlike the former, the mechanism of vacuolar acidification in soybean remains uncharacterized at the molecular level. To investigate this mechanism, we isolated four recessive purple–blue EMS-induced flower mutants from the purple flower soybean cultivar, Pungsannamul. The petals of all the mutants had increased pH compared with those of wild Pungsannamul. One of the mutants had a single nucleotide substitution in GmPH4, a regulator gene encoding an MYB transcription factor, and the substitution resulted in a premature stop codon in its first exon. The other three mutants had nucleotide substitutions in GmPH5, a single new gene that we identified by physical mapping. It corresponds to Glyma.03G262600 in chromosome 3 and encodes a proton pump that belongs to the P3A-ATPase family. The substitutions resulted in a premature stop codon, which may be a defect in the ATP-binding capacity of GmPH5 and possibly a catalytic inefficiency of GmPH5. The result is consistent with their genetic recessiveness as well as the high pH of mutant petals, suggesting that GmPH5 is directly involved in vacuolar acidification. We also found that the expression of GmPH5 and several putative “acidifying” genes in the gmph4 mutant was remarkably reduced, indicating that GmPH4 may regulate the genes involved in determining the vacuolar pH of soybean petals.